Entre a sucessão e a república: representações da Princesa Isabel e projeções para o terceiro reinado - Pereira, Cibele Camargos (2023)
The 1880s was a scenario for the reinforcement of the republican movement, for the realization of the abolition of slavery, and for the development of publicity for the dynastic succession in the format of the Brazilian Third Reign of the Imperial Princess Isabel de Bragança. The Brazilian political and social context experienced a process of ruptures and transformations characterized by the spread of positivist ideas, in which elite political's members project different futures for the young nation. The periodical press replayed the notices about the emperor's illness from the mid-1880s, producing different political projections for Brazil. While the monarchists pursued the prestige and legitimacy for the possible Reign of Princess Isabel, the republicans reclaimed the monarch's fragility and the system's vulnerability. They attacked the Imperial Princess Isabel, responsible for the Bragança Kingdom perpetuation. In the exercise of the Kingdom, pending the monarch's illness, the crown's heir solidified her participation in the abolitionist movement. In this context, she developed her autonomy as regent and successor, awakening at the same time popular support and rejection as heir of the crown in the virtual Third Reign.